2013
DOI: 10.1007/s00382-013-1921-7
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced western North Pacific tropical cyclone activity in May in recent years

Abstract: The tropical cyclone (TC) power dissipation index (PDI) in May over the western North Pacific (WNP) region shows a remarkable increase from the pre-1999 years to the post-1999 years (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011). Both increased TC numbers and enhanced TC intensity contributed to the change in the PDI. The averaged TC number in May increased from 1.05 per year in the pre-1999 years to 1.75 per year in the post-1999 years. In particular, the number of intense typhoon g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 24 publications
(21 reference statements)
2
17
0
Order By: Relevance
“…It has been widely adopted to investigate issues related to climate change (Kwon et al 2007;Liu et al 2011;Xu and Wang 2014). The Lepage test statistic [HK, the same as used by Yonetani and McCabe (1994)] is represented by a combination of the standardized Wilcoxon's (W) and Ansari-Bradley's (A) statistics…”
Section: B Methods Of Changepoint Detection For Decadal Changementioning
confidence: 99%
See 2 more Smart Citations
“…It has been widely adopted to investigate issues related to climate change (Kwon et al 2007;Liu et al 2011;Xu and Wang 2014). The Lepage test statistic [HK, the same as used by Yonetani and McCabe (1994)] is represented by a combination of the standardized Wilcoxon's (W) and Ansari-Bradley's (A) statistics…”
Section: B Methods Of Changepoint Detection For Decadal Changementioning
confidence: 99%
“…3a), which is triggered by the zonal SST gradient between the cold SCS and the warm NIO. The anomalous easterly flow suppresses the ISV activity and reduces the synoptic-scale disturbances over the SCS (Xu and Wang 2014), contributing to the decrease in TC activity during 2003-11. The above analysis demonstrates that the suppressed ISV activity is also a critical factor that affects the decadal reduction in the SCS TC activity occurring around the early 2000s.…”
Section: Possible Role Of the Scs Isvmentioning
confidence: 97%
See 1 more Smart Citation
“…The Lepage test technique is a common method used to detect quantitatively the significance of abrupt climate change points (Lepage, 1971). This technique has been widely employed to investigate issues related to decadal changes (e.g., Liu et al, 2011;Xu and Wang, 2014;Cao et al, 2019). A 9-year window is chosen to detect the decadal change using this method.…”
Section: Methods Of Change Point Detectionmentioning
confidence: 99%
“…Stowasser et al (2007) indicates a continued trend towards higher proportion of the most intense TCs under future warming scenarios. Shibin and Bin (2013) found that the recent increase of TC numbers in the West North Pacific in May is the result of an enhanced summer monsoon over the South Asia and SCS.…”
Section: Introductionmentioning
confidence: 99%